Early experience with laparoscopic extralevator abdominoperineal excision within an enhanced recovery setting: analysis of short-term outcomes and quality of life - Vaughan-Shaw, PG (The Royal College of Surgeons of England, 2011)
INTRODUCTION: Conventional abdominoperineal excision for low rectal cancer has a higher local recurrence and reduced survival compared to anterior resection. An extralevator abdominoperineal excision (ELAPE) may improve outcome through removal of increased tissue in the distal rectum. Experience with ELAPE is limited and no studies have reported on quality of life (QOL) following this procedure. We describe a minimally invasive approach to ELAPE within an enhanced recovery programme, and present short-term results and QOL analyses. METHODS: All laparoscopic ELAPEs were included in a prospective database. Demographics, intra-operative and post-operative outcomes were evaluated. Postoperative QOL was assessed using the European Organisation for Research and Treatment of Cancer (EORTC) questionnaires QLQ-C30 and QLQ-CR29. RESULTS: Thirteen laparoscopic ELAPEs were performed over a two-year period. All were enrolled in an enhanced recovery programme. The median age was 76. The median tumour height was 20mm (range: 0–50mm) from the dentate line and all patients received neoadjuvant treatment. The median duration of surgery was 300 minutes (range: 120–488 minutes), the mean blood loss was 150ml and one procedure was converted to open surgery. There was no circumferential resection margin involvement or tumour perforation. The median duration of use of intravenous fluid, patient controlled analgesia and urinary catheterisation was 2, 2 and 2.5 days respectively and the median length of hospital stay was 7.5 days. Two patients developed perineal wound dehiscence. QOL analysis revealed high global health status (90.8), physical (91.3), emotional (98.3) and social functioning (100) scores, which compared favourably with EORTC reference values and published QOL scores following conventional abdominoperineal excision. CONCLUSIONS: Laparoscopic ELAPE within an enhanced recovery setting is a feasible and safe approach with acceptable short-term outcomes and post-operative quality of life.